Local Wisdom Management to Maintain the Local Environment (A Study of the Naga Baru Klinting folklore in Rawa Pening Ambarawa) - Hari Suryanto; Retnowati Retnowati; Purwanto Purwanto (AIBPM Publisher, 2020)
Folklore that wecan find in Nusantara (Indonesian archipelago) has its uses as an educational tool to remind us of an event and the name of a place and to entrust a message of prohibition and a moral message, a social protest, a hope, and an environmental protection. Naga Baru Klinting is a folklore developed in Ambarawa, Central Java. Rawa Pening is an area where the folklore is told. This oral folklore is one proof of the nobleness and high achievements of cultural science that were accepted by the ancient society. The value management system is delivered in the form of a story based on environmental and social conditions regarding the Naga Baru Klinting folklore. The concept of life that still upholds the relationship between ManNature-God makes life harmonious. Unfortunately, however, Rawa Pening is currently facing a situation resulted from the water hyacinth plants and waste that pollute the water. Naga Baru Klinting folklore has a moral message of controlling oneself to ensure personal safety in order to prevent an individual from doing improper actions. With a management system through folklore, it is expected to restore public awareness to conserve and care for natural resources and the environment as a supporting life force which brings goodness and prosperity to the local people and entire nation.